Chapter 10 Values and Participation of Individuals Without Mental Capacity in Hong Kong - Cheung, Daisy (Bristol University Press, 2023)
The digital PDF and EPUB versions of chapter 10 are available Open Access and distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence (https://creativecommons.org/licenses/by-nc-nd/4.0/). With contributions from an international team of experts, this collection provides a much-needed international, comparative approach to mental capacity law. The book focuses particularly on exploring substantive commonalities and divergences in normative orientation and practical application embedded in different legal frameworks. It draws together contributions from eleven different jurisdictions across Europe, Asia and the UK and explores what productive or unproductive values and practices currently exist.